2022
DOI: 10.1371/journal.pntd.0009585
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity of catalytic and lectin-like domain of Trypanosoma congolense trans-sialidase modulates its catalytic activity

Abstract: Trans-sialidases (TS) represent a multi-gene family of unusual enzymes, which catalyse the transfer of terminal sialic acids (Sia) from sialoglycoconjugates to terminal galactose or N-acetylgalactosamine residues of oligosaccharides without the requirement of CMP-Neu5Ac, the activated Sia used by typical sialyltransferases. Enzymes comprise a N-terminal catalytic domain (CD) followed by a lectin-like domain (LD). Most work on trypanosomal TS has been done on enzymatic activities focusing on the CD of TS from T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 51 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…Whether or not TconTS1 requires N-glycosylation for accurate protein folding cannot be excluded by our experiments, and the role of N-glycans in TconTS folding still needs to be investigated. However, as discussed above our findings on enzymatic activity of bacterially expressed TconTS provide evidence for glycosylation-dependent misfolding of the enzymes (34). Further thermodynamic details of the denaturation processes for the two enzyme forms could be investigated in future works with methods complementary to CD, such as calorimetry.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Whether or not TconTS1 requires N-glycosylation for accurate protein folding cannot be excluded by our experiments, and the role of N-glycans in TconTS folding still needs to be investigated. However, as discussed above our findings on enzymatic activity of bacterially expressed TconTS provide evidence for glycosylation-dependent misfolding of the enzymes (34). Further thermodynamic details of the denaturation processes for the two enzyme forms could be investigated in future works with methods complementary to CD, such as calorimetry.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, the approach of site-directed glycosylation knockout also has its limitations. Furthermore, for TconTS the orders of magnitude lower specific activity of enzyme expressed in bacteria relative to that expressed by CHO-Lec1 cells provide evidence for misfolding of the enzyme as a consequence of absence of N -glycans (34). Since TconTS1 exhibits nine putative N- glycosylation sites, a first assessment of which sites might be more important than others for enzyme function was desirable and aimed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like all TS, TconTS1 consists of an N-terminal catalytic domain responsible for the transfer of Sia, and of a C-terminal lectin-like domain whose biological function remains unclear. Recently, we demonstrated that the TconTS lectinlike domain can modulate enzymatic activity (37). The catalytic and lectin-like domain are connected via an α-helix (Fig.…”
Section: Introductionmentioning
confidence: 99%